Perancangan Model Penjadwalan Teknisi pada Perawatan BD Check Pesawat Airbus dengan Memperhitungkan Beban Kerja - Syafitri, Adelia; Hidayat, Syarif (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
PT GMF AeroAsia is engaged in the maintenance, repair, and overhaul (MRO) of aircraft. It is known that GMF is the largest domestic MRO company at 30% while 70% is owned by foreign MRO companies. Based on the company's vision to make the company a world-class MRO, it is necessary to develop a business scheme in terms of capability, quantity, and quality. However, the scheduling of technicians in carrying out aircraft maintenance is currently unable to meet the demand every hour due to the uncertain flight schedule of the aircraft every day so that the workload of each technician exceeds the normal workload. The calculation of the workload using the full-time equivalent method showed that the workload of technicians was overloaded so that an additional number of technicians was needed, as well as analyzing the causes and consequences of the excessive workload of technicians using the fishbone diagram method and modeling the formulation of the technician scheduling problem that works in maintenance before departure check Airbus aircraft in the form of integer linear programming with decision variables such as the number of technicians, the number of shifts and the number of working days, then the constraint function is the constraints to be achieved in modeling, and the objective function is to minimize the number of technicians employed. Furthermore, the model is implemented using the LINGO 19.0 software so that it is found that the model can produce an optimal technician schedule in scheduling.Keywords - Fishbone Diagram, Full Time Equivalent, Integer Linear Programming, Lingo Software, Matchematical Modeling, Scheduling, Workload